AKRB POLA KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI DINAS KOMUNIKASI INFORMATIKA DAN PERSANDIAN KOTA YOGYAKARTA - Ajeng Pratiwi Defitri; Ardiyanto Wardhana (AKADEMI KOMUNIKASI RADYA BINATAMA, 2024)
ABSTRACTCommunication is one of the most important aspects in life. Communicationactivities include conveying and receiving information, ideas and feedback. In anorganization, communication plays a role in uniting the interests of all members to achieve acommon goal. Communication is the